Stakeholder attitudes towards the role and application of informed consent for newborn bloodspot screening: a study protocol - Nicholls, S G (BMJ Open, 2014)
INTRODUCTION:  Newborn bloodspot screening (NBS) involves testing a small sample of blood taken from the heel of the newborn for a number of serious and life-limiting conditions. In Canada, newborn screening programmes fall under provincial and territorial jurisdiction with no federal coordination. To date, we know very little about the underlying beliefs around different consent practices or how terminology is interpreted by different individuals. Differences in attitudes may have important healthcare consequences. This study will provide empirical data comparing stakeholder opinions on their understanding of consent-related terminology, the perceived applicability of different consent approaches to newborn screening, and the requirements of these different approaches. METHODS AND ANALYSIS: Parents, healthcare professionals and policymakers will be recruited in the provinces of Ontario and Newfoundland and Labrador. Parents will be identified through records held by each provincial screening programme. Healthcare professionals will be purposively sampled on the basis of engagement with newborn screening. Within each province we will identify policymakers who have policy analysis or advisory responsibilities relating to NBS. Data collection will be by qualitative interviews. We will conduct 20 interviews with parents of young children, 10 interviews with key healthcare professionals across the range of appropriate specialties and 10 with policymakers at each site (40 per site, total, N=80). The examination of the transcripts will follow a thematic analysis approach. Recruitment started in June 2014 and is expected to be complete by June 2015. ETHICS AND DISSEMINATION: This study received ethics approval from the Ottawa Health Science Network Research Ethics Board, the Children's Hospital of Eastern Ontario Research Ethics Board (both Ontario), and the Health Research Ethics Authority (Newfoundland and Labrador). RESULTS: These will be reported in peer-reviewed publications and conference presentations. The results will have specific application to the development of parent education materials for newborn screening.